Pengaruh Brand Awareness Terhadap Minat Beli Konsumen Studi Pembelian Produk Skintific - Ira Juwita Baya; Vitria Puri Rahayu; Sutrisno Sutrisno; Indah Permatasari (Educational Studies: Conference Series, 2025)
This study aims to determine the effect of brand awareness on the purchase intention of Skintific products among students of the Economic Education Study Program at Mulawarman University. The study employs a quantitative approach with a causal associative method. A total of 84 students were selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using descriptive analysis, classical assumption tests, simple linear regression, t-test, and coefficient of determination with the assistance of the JASP program. The results show that brand awareness influences the purchase intention of Skintific products. The higher the level of brand awareness, the greater the likelihood that consumers will purchase Skintific products. High brand awareness enhances consumers’ trust and confidence in the quality and benefits of the product and helps them recognize and recall the Skintific brand compared to its competitors. This study provides an important contribution for companies in designing effective marketing strategies by emphasizing the enhancement of brand awareness as a key factor in increasing consumer purchase intention. Keywords: Brand Awareness, Consumer Purchase Intention, Skintific Product Penelitian ini bertujuan untuk mengetahui pengaruh brand awareness terhadap minat beli produk Skintific pada mahasiswa Program Studi Pendidikan Ekonomi Universitas Mulawarman. Penelitian menggunakan pendekatan kuantitatif dengan metode asosiatif kausal. Sampel sebanyak 84 mahasiswa dipilih melalui teknik purposive sampling. Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis dengan analisis deskriptif, uji asumsi klasik, regresi linier sederhana, uji t, dan koefisien determinasi menggunakan program JASP. Hasil penelitian menunjukkan bahwa brand awareness berpengaruh terhadap minat beli produk Skintific. Semakin tinggi tingkat kesadaran merek, semakin besar kemungkinan konsumen untuk membeli produk Skintific. Kesadaran merek yang tinggi meningkatkan rasa percaya dan keyakinan terhadap kualitas serta manfaat produk, serta membantu konsumen mengenali dan mengingat merek Skintific dibandingkan pesaingnya. Penelitian ini memberikan kontribusi penting bagi perusahaan dalam merancang strategi pemasaran yang efektif dengan menekankan peningkatan brand awareness sebagai kunci untuk meningkatkan minat beli konsumen. Kata Kunci: Brand Awareness, Minat Beli Konsumen, Produk Skintific